Network-Embedded Management and Applications Understanding Programmable Networking Infrastructure - Clemm, Alexander; Wolter, Ralf (Springer New York : Imprint: Springer, 2013)
Despite the explosion of networking services and applications in the past decades, the basic technological underpinnings of the Internet have remained largely unchanged. At its heart are special-purpose appliances that connect us to the digital world, commonly known as switches and routers. Now, however, the traditional framework is being increasingly challenged by new methods that are jostling for a position in the next-generation Internet. The concept of a network that is becoming more programmable is one of the aspects that are taking center stage. This opens new possibilities to embed software applications inside the network itself and to manage networks and communications services with unprecedented ease and efficiency. In this edited volume, distinguished experts take the reader on a tour of different facets of programmable network infrastructure and application exploit it. Presenting the state of the art in network embedded management and applications and programmable network infrastructure, the book conveys fundamental concepts and provides a glimpse into various facets of the latest technology in the field.